Better functional recovery after acute stroke in older patients managed in a new dedicated post-stroke geriatric unit compared to usual management - Bruno Oquendo; Charlotte Nouhaud; Witold Jarzebowski; Anne Leger; Christel Oasi; Massamba Ba; Carmelo Lafuente-Lafuente; Joel Belmin (Elsevier, 2024)
Objectives: A Stroke care Pathway dedicated to the ELders (SPEL) for patients with acute stroke was created in 2013 at the hospitals Pitié-Salpêtrière-Charles Foix (Paris, France). It is characterized by a stroke unit dedicated to emergency stroke care, and a post stroke geriatric unit (PSGU) including rehabilitation and management of geriatric syndromes. The aim of the study was to compare the functional recovery of patients transferred to PSGU versus other rehabilitation care in patients over 70 years of age after stroke. Design: A cohort observational study over a 4-year period. Setting: Hospitals Pitié-Salpêtrière and Charles Foix (Paris, France). Participants: We studied patients over 70 years admitted to the participating stroke unit for acute stroke consecutively hospitalized from January 1, 2013, to January 1, 2017. Intervention: Patients transferred in the PSGU were compared to those admitted in other rehabilitation units. Measurements: The primary outcome was 3-month functional recovery after stroke. The secondary outcomes were the hospital length of stay and the returning home rate. A multivariable logistic regression was applied to adjust for confounding variables (age, sex, NIHSS score and Charlson's comorbidity score). Results: Among the 262 patients included in the study, those in the PGSU were significantly older, had a higher Charlson's comorbidity score and a higher initial NIHSS severity score. As compared to the other patients, functional recovery at 3 months was better in the PSGU (Rankin's score decreased by 0.80 points versus 0.41 points, p = 0.01). The average total length of stay was reduced by 16 days in the patients referred to the PSGU (p = 0.002). There was no significant difference in the returning home rate between the two groups (p = 0.88). Conclusion: The SPEL which includes a post-stroke geriatric unit (PSGU) has been associated with improved recovery and had a positive impact in the management of older post-stroke patients.